The Role of Hypoxia in Orthodontic Tooth Movement - A. Niklas; P. Proff; M. Gosau; P. Römer (Hindawi Limited, 2013)
Orthodontic forces are known to have various effects on the alveolar process, such as cell deformation, inflammation, and circulatory disturbances. Each of these conditions affecting cell differentiation, cell repair, and cell migration, is driven by numerous molecular and inflammatory mediators. As a result, bone remodeling is induced, facilitating orthodontic tooth movement. However, orthodontic forces not only have cellular effects but also induce vascular changes. Orthodontic forces are known to occlude periodontal ligament vessels on the pressure side of the dental root, decreasing the blood perfusion of the tissue. This condition is accompanied by hypoxia, which is known to either affect cell proliferation or induce apoptosis, depending on the oxygen gradient. Because upregulated tissue proliferation rates are often accompanied by angiogenesis, hypoxia may be assumed to fundamentally contribute to bone remodeling processes during orthodontic treatment.